Child Neurology: Case Report of Lambl Excrescences in a Pediatric Patient With Multifocal Strokes. (12th July 2022) - Robertson, Dwight M.; Wright, Melissa A.; Ostrander, Betsy; Tani, Lloyd Y.
Abstract : Lambl excrescences are fibrinous connective tissue strands found predominantly on left-sided cardiac valves. These valvular strands are typically benign, but have been implicated as a potential etiology of embolic strokes in adult patients. The significance of Lambl excrescences in pediatric stroke cases is unclear and not previously reported in the literature. In this study, we describe a 10-year-old boy who presented with acute-onset right-sided hemiplegia, found to have multifocal embolic strokes of various ages. Extensive stroke workup was unrevealing, aside from the presence of small, filamentous, strand-like densities associated with the mitral and aortic valves noted on a transesophageal echocardiogram consistent with Lambl excrescences. In this case report, we review Lambl excrescences and their significance in acute stroke and management options for the prevention of future ischemia in these patients.